Ramsey numbers for graph sets versus complete graphs - Faudree, Ralph; Harborth, Heiko; Mengersen, Ingrid (Utilitas Mathematica, 1996)
The set Ramsey number rn(k, (n2) ) is the smallest integer r such that if the edges of a complete graph Kr are 2-colored, then there will be a graph with n vertices and k edges in the first color or a graph with n vertices and (n2) (e.g. a complete graph) in the second color. For each n ≥ 3 and 1 ≤ k ≤ n, the set Ramsey numbers rn(k, (n2)) are determined.